From COVID-19. New and Old Orders in Migration in Tijuana, Northern Border of Mexico - Castro Neira, Yerko (2024)
This article presents a detailed review of what happened as a result of the COVID-19 pandemic on the northern border of Mexico, particularly in the city of Tijuana. The objective is to explain the fundamental changes in the forms of migratory control and the responses designed by organizations and migrants. The work is based on the application, during 2022, of in-depth interviews with activists and migrant defenders as well as with migrants. The results show that, with the pandemic, the relationships between civil society organizations, international agencies and state actors have changed. In this sense, migration control became more efficient and rational, as well as more inhumane and cruel. At the same time, the results reveal that it was the organizations that provided the main responses and forms of accompaniment.